Tantangan Hukum dan Keamanan dalam Mitigasi Sampah Luar Angkasa Tak Teridentifikasi: Ancaman bagi Misi Antariksa dan Keselamatan Astronaut - Nurul Adzkia; Erzavin Daveri; Ema Septaria; M. Ilham Adepio; Rahwa Wati, Linda (Indonesian Journal of Law and Justice, 2025)
Unidentified space debris poses a significant threat to the sustainability of space exploration and the safety of astronauts. As the number of artificial objects in Earth's orbit increases, the risk of collisions and damage to operational satellites and spacecraft also grows. This study examines the legal and security challenges in mitigating unidentified space debris using a normative approach, analyzing key international treaties such as the Treaty on Principles Governing the Activities of States in the Exploration and Use of Outer Space, including the Moon and Other Celestial Bodies (Outer Space Treaty 1967), the Convention on International Liability for Damage Caused by Space Objects 1972 (Liability Convention 1972), and the Agreement on the Rescue of Astronauts, the Return of Astronauts and the Return of Objects Launched into Outer Space 1967 (Rescue Agreement 1967). While these treaties establish a legal framework for space object responsibility, gaps remain in ownership attribution and enforcement mechanisms, particularly for unidentified debris. Additionally, limited monitoring technology hampers effective collision risk mitigation. To address these challenges, stronger international regulations, the development of more precise tracking technologies, and enhanced global cooperation in space debris removal efforts are essential to maintaining the safety and sustainability of future space missions.